USING ENGLISH COMMEDY MOVIES WITH PEER SUPPORT IN TEACHING SPEAKING - Rahmatul Ukhra; Bustami Usman; Asnawi Muslem (Universitas Syiah Kuala, 2020)
The study aimed to investigate the effects of using comedy movies with peer support on students’ speaking skills and students’ responses toward the implementation of using comedy movies with peer support. In doing this, 60 students of class X at SMAN 2 Peusangan Bireuen were chosen as the samples. The data were collected by giving tests and questionnaires. The data from the speaking test were analyzed by using IBM Statistic SPSS version 23. Meanwhile, the data from questionnaires were analyzed by using a percentage formula. The finding revealed that there was a significant difference in the post-test scores of the students who were taught speaking by using comedy movies with peer support strategies and those who were taught speaking without using comedy movies with peer support strategy. The mean score of the posttest on the experimental group was 75.93. Meanwhile, the mean score of posttest on the control group was 67.50. The result of the t-test score showed the score difference was significant (-1.96 9.50 1. 96). Moreover, the students gave positive responses toward using comedy movies with peer support in teaching speaking. They also faced some difficulties in learning speaking by using comedy movies with peer support strategy. In fact, they admitted that they lacked of confidence, vocabulary, and comprehension because of having a very limited time to practice speaking.